RMRP accelerates ligamentum flavum hypertrophy by regulating GSDMD-mediated pyroptosis through Gli1 SUMOylation - Yan, Xudong; Liu, Tinglong; Zhang, Run; Ma, Qinghong; Sun, Chao (Frontiers in Immunology, 2024)
Hypertrophy of ligamentum flavum (LF) is a significant contributing factor to lumbar spinal canal stenosis (LSCS). lncRNA plays a vital role in organ fibrosis, but its role in LF fibrosis remains unclear. Our previous findings have demonstrated that Hedgehog-Gli1 signaling is a critical driver leading to LF hypertrophy. Through the RIP experiment, our group found lnc-RMRP was physically associated with Gli1 and exhibited enrichment in Gli1-activated LF cells. Histological studies revealed elevated expression of RMRP in hypertrophic LF. In vitro experiments further confirmed that RMRP promoted Gli1 SUMO modification and nucleus transfer. Mechanistically, RMRP induced GSDMD-mediated pyroptosis, proinflammatory activation, and collagen expression through the Hedgehog pathway. Notably, the mechanical stress-induced hypertrophy of LF in rabbit exhibited analogous pathological changes of LF fibrosis occurred in human and showed enhanced levels of collagen and α-SMA. Knockdown of RMRP resulted in the decreased expression of fibrosis and pyroptosis-related proteins, ultimately ameliorating fibrosis. The above data concluded that RMRP exerts a crucial role in regulating GSDMD-mediated pyroptosis of LF cells via Gli1 SUMOylation, thus indicating that targeting RMRP 2 could serve as a potential and effective therapeutic strategy for LF hypertrophy and fibrosis.